Attitudes and Adoption of Rainwater Harvesting: Influence of Gender, Awareness, and Social Status - Michae Kanyi; David E. Lawver; Jonathan Ulmer; Mary Murimi; Mary Murimi (Journal of International Agricultural and Extension Education, 2017)
Inadequate potable water often leads to hygiene-related infections while general lack of water for agriculture is a precursor to malnutrition in Sub-Saharan Africa. There is a widespread low adoption of rooftop rainwater harvesting in Kenya. Attitudes influence the level of farmers’ participation in water harvesting. Literature on the influence of gender, level of education, and socioeconomic status (SES) on attitudes toward rainwater harvesting among smallholder farmers is inadequate. This study was conducted to fill that knowledge gap. The study was conducted in four sub-counties in Kenya. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 20. Level of significance was set at α = .05. Effect size was calculated and presented as Cohen’s d for the independent t-tests and as omega squared (ω2) for the one-way ANOVA. Post hoc tests were conducted using Gabriel’s procedure. Results indicated that women had statistically significant better attitudes toward rainwater harvesting than men. Level of formal education among smallholder farmers did not indicate a statistically significant difference in attitudes. Comparisons across SES levels indicated a statistically significant difference in attitudes toward rainwater harvesting. Attitudes were determined to be a statistically significant predictor of adoption of rainwater harvesting. The researchers envision that these findings will be helpful to program planners, policy makers, agricultural educators, and curriculum designers in Kenya. The study expounded on knowledge on demographic-related attitudinal barriers to prioritization and adoption of rainwater harvesting. Recommendations to policy makers and educators on enhanced extension and outreach programs were proposed. Involvement of women as change agents was recommended. Further research on suitable and relevant extension methods was recommended
Keywords: Adoption; attitudes; education; rainwater harvesting; socioeconomic status